2012
DOI: 10.1590/s0100-204x2012000600019
|View full text |Cite
|
Sign up to set email alerts
|

Uso de probióticos na produção de pós-larvas de camarão-rosa

Abstract: Resumo -O objetivo deste trabalho foi avaliar o uso de probióticos na produção de pós-larvas do camarão-rosa (Farfantepenaeus brasiliensis). Utilizou-se o delineamento experimental inteiramente casualizado, com dois tratamentos -uso de probióticos (Bacillus spp.) e controle com uso de antibiótico (eritromicina) -e quatro repetições. Pós-larvas no estágio PL 1 foram estocadas em cada parcela experimental (3,0 L) e cultivadas até o estágio PL 10 . As variáveis de qualidade de água e o desenvolvimento de bactéria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
3
1
Order By: Relevance
“…Within 168 hours, a lower amount of nitrite was observed in T2 when compared to the control, which can be related to the absence of nitrifying bacteria (Nitrosomonas and Nitrobacter) (Chen et al 2006) caused by the action of antibiotics. This result contradicts the findings of Silva et al (2012), who found that nitrite was significantly higher in the treatment with antibiotic, but did not affect the development of Penaeus (=Farfantepenaeus) brasiliensis Latreille 1817.…”
Section: Discussioncontrasting
confidence: 94%
“…Within 168 hours, a lower amount of nitrite was observed in T2 when compared to the control, which can be related to the absence of nitrifying bacteria (Nitrosomonas and Nitrobacter) (Chen et al 2006) caused by the action of antibiotics. This result contradicts the findings of Silva et al (2012), who found that nitrite was significantly higher in the treatment with antibiotic, but did not affect the development of Penaeus (=Farfantepenaeus) brasiliensis Latreille 1817.…”
Section: Discussioncontrasting
confidence: 94%
“…ix) It is necessary to evaluate the water quality (ammonia, nitrite, nitrate, phosphate, sulfate) and estimate possible changes in the use of antimicrobials in culture medium caused by the withdrawal of bacteria. The bacterioplankton is responsible for nutrient cycling, and its removal could result in the accumulation of nutrients to toxic levels (Alongi, 1994;Silva et al, 2012). x) Make sure to process and appropriately dispose of the culture and the production medium with antimicrobials avoiding environmental contamination and/or bacteria resistance.…”
Section: Future Directions: Remarks and Conclusionmentioning
confidence: 99%
“…However, other organisms, such as fungi and yeasts, have also been used for probiotic purposes (Devajara et al, 2002;Ribeiro et al, 2008). Research on probiotics for aquatic animals is increasing with the demand for sustainable, environmentally friendly aquaculture (Wang et al, 2005;Farzanfar, 2006;Ravi et al, 2007;Decamp et al, 2008;Li et al, 2008;Gomez et al, 2009;Guo et al, 2009;Liu et al, 2009;Ninawe & Selvin, 2009;Peraza-Gómes et al, 2009;Pai et al, 2010;Shen et al, 2010;Silva et al, 2011Silva et al, , 2012Souza et al, 2011;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%